Eksplorasi Modul Noetherian - Umam, Ashadul; Mifftahurrahman, Mifftahurrahman; Pratiwi, Lia Fitta (Semeton Mathematics Journal, 2025)
Noetherian Modules are a fundamental concept in algebra, providing a structured framework for studying algebraic structures. These modules satisfy the ascending chain condition (ACC), which ensures that every ascending chain of submodules terminates after a finite number of steps. This article explores the definition, key properties, and applications of Noetherian modules in ring theory, homological algebra, and algebraic topology. Through this discussion, it is demonstrated that Noetherian Modules play a crucial role in analyzing ideal structures and more complex algebraic representations. The article also provides concrete examples to illustrate the properties and significance of Noetherian modules across various branches of algebra.